2015
DOI: 10.1038/ncomms9853
|View full text |Cite
|
Sign up to set email alerts
|

PH motifs in PAR1&2 endow breast cancer growth

Abstract: Although emerging roles of protease-activated receptor1&2 (PAR1&2) in cancer are recognized, their underlying signalling events are poorly understood. Here we show signal-binding motifs in PAR1&2 that are critical for breast cancer growth. This occurs via the association of the pleckstrin homology (PH) domain with Akt/PKB as a key signalling event of PARs. Other PH-domain signal-proteins such as Etk/Bmx and Vav3 also associate with PAR1 and PAR2 through their PH domains. PAR1 and PAR2 bind with priority to Etk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 70 publications
(82 reference statements)
4
28
0
Order By: Relevance
“…The findings presented here are surprising in that the preponderance of the literature suggests that PAR‐1 promotes tumor progression. This conclusion is based on in vitro analyses, which may be limited by factors such as the lack of tumor–stromal cell interaction , as well as multiple detailed in vivo analyses based on highly specific PAR‐1 inhibitors , or genetic manipulation of PAR‐1 in tumor cells or stromal cells . Further complicating the picture, analyses of a murine model of spontaneously developing breast carcinoma demonstrated no impact of PAR‐1 deletion on tumor progression .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings presented here are surprising in that the preponderance of the literature suggests that PAR‐1 promotes tumor progression. This conclusion is based on in vitro analyses, which may be limited by factors such as the lack of tumor–stromal cell interaction , as well as multiple detailed in vivo analyses based on highly specific PAR‐1 inhibitors , or genetic manipulation of PAR‐1 in tumor cells or stromal cells . Further complicating the picture, analyses of a murine model of spontaneously developing breast carcinoma demonstrated no impact of PAR‐1 deletion on tumor progression .…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have led to a widely held view that PAR‐1 activation drives cancer progression, and PAR‐1 activation has been proposed as one of the mechanisms coupling thrombin‐mediated proteolysis to cancer progression . Although many of the available data supporting this conclusion are based on in vitro analyses , there are ample in vivo analyses based on either specific PAR‐1 inhibitors or genetic manipulation of PAR‐1 in tumor cells or stromal cells . However, the majority of the in vivo data regarding the role of PAR‐1 in malignancy are based on analyses of fully transformed tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…66 There are in vivo studies that support the view that PAR-1 drives tumor growth that are based on well-established, highly specific PAR-1 inhibitors, 67 as well as genetic manipulation of PAR-1 in tumor cells or stromal cells. 49,[68][69][70][71][72][73][74] While these studies convincingly demonstrate a role for PAR-1 in driving tumor progression, the paradigm is clearly not universal. Analyses of a murine model of spontaneously developing breast carcinoma in gene-targeted PAR-1-deficient mice failed to demonstrate any role whatsoever for PAR-1 in this experimental context.…”
Section: Thrombin and Par-1 Signaling In Tumorigenesis And Tumor Growthmentioning
confidence: 97%
“…Mueller and colleagues presented evidence that thrombin-enhanced migration of melanoma cells is driven by PAR1 and PAR2, in a manner consistent with the "direct transactivation" of PAR2 by thrombin-activated PAR1. (23) Bar-Shavit has also reported synergistic effects of PAR1 and PAR2 activation in tumor development (24,25) Kuliopulos reported that signaling by PAR1-PAR2 heteromers may be implicated in restenosis, the dangerous narrowing of blood vessels which occurs in a significant fraction of patients after percutaneous interventions (PCIs). (26) We hypothesize that heterobivalent antagonists may act selectively at putative PAR1-PAR2 heteromers and thus may act to inhibit cancer cell metastasis and proliferative processes such as restenosis, while minimizing impacts on normal PAR signaling.…”
mentioning
confidence: 99%